Mechanical properties and deformation behavior of additively manufactured TiC nanoparticles reinforced Nb at 1000 °C - Da Liu; Yuanyuheng Wang; Wei Liu; Youxing Yu; Jiangbo Sha (Journal of Materials Research and Technology)
Additive manufacturing enables the creation of complex geometries, particularly in the production of Nb alloys for aerospace applications, which are challenging to process using conventional methods. In this study, TiC nanoparticles were selected as nucleants and assembled onto Nb powders. Using laser-directed energy deposition (L-DED) technology, we successfully achieved crack-free Nb-xTiC alloys (where TiC is a nanoparticle and x = 0, 1, 2 and 3 wt%, and referred as to Nb–0TiC, Nb–1TiC, Nb–2TiC and Nb–3TiC alloys, hereafter). The microstructural characteristics, hardness, tensile properties at 1000 °C and deformation behavior of the Nb-xTiC alloys, as well as the crystallographic orientation relationship of the Nb-carbide (α-Nb2C) couple, have been thoroughly investigated. The microstructure consists of near-equiaxed Nb matrix and α-Nb2C carbides (0.3–1.5 μm in width, 0.4–5 μm in length), which are found both along grain boundaries and within the grain interior. The L-DED Nb-xTiC alloy exhibited a high plastic elongation of 16.3 % while the ultimate tensile strength increased significantly to 318 MPa at 1000 °C as the TiC content increased from 0 % to 2 wt%. This outstanding combination of high-temperature strength and ductility at 1000 °C can be results from the synergistic effect of the high-density tangled dislocation pile-up around the α-Nb2C precipitates, the presence of SF networks and L-C locks within the α-Nb2C, the movable mixed dislocations and the kink bands within the Nb grains.